Food delivery ordering system / Nur Shafika Izani Mohamad Aseri and Siti Nurul Hayatie Ishak - Mohamad Aseri, Nur Shafika Izani; Ishak, Siti Nurul Hayatie (2020)
Online food ordering system is a web-based application that allows customers to order their foods online by locating restaurant around their neighbourhood. Recently, this trend becomes popular among university student. Student placed order typically through a merchant's website or phone call, while some students join an instant messaging group to make order. Current practice leads to the problems such as difficulty to track and manage order, lack of merchant and meals information and some student experienced fraud. Thus, a food delivery ordering system (FDOS) is developed which act as an e-marketplace for student and merchant to conduct transaction and this process is controlled by the university in a single platform. The objective of this project includes identifying user and system requirements, development of the system using adapted waterfall model and applying characteristics of online demand delivery services and the last objective is to evaluate the functionality and usability of the system with expert and potential users. FDOS utilized a business-to-consumer (B2C) model in line with the commission fee as a revenue model. The evaluation process includes seven (7) constructs which are online food ordering system, perceived ease of use, efficiency, satisfaction, consistency, user interface design and restaurant perception. As a result, the construct for online food ordering system and restaurant perception get the highest mean which is 4.97 and 5.0 respectively. Conclusively, users of the system are satisfied that online food ordering system is more convenient and helps merchant to increase company growth to accelerate revenue.